Non-equivalence at word level in the English translation of Fuadi’s Rantau 1 Muara - Iwik Pratiwi (Jurnal Linguistik Terapan, 2013)
Rantau 1 Muara is the last novel of the trilogy is the last trilogy of Negeri 5 Menara, written by Anwar Fuadi. The novel settings include, one of them, the unique life of pesantren. Because it is so unique, the translation into English may face problems as many of the concepts talked about are bound to Javanese or Islamic culture. Thus, it can be predicted that some problems should appear. To prove this, the writer translates one chapter and report the problem and how to solve the problems. This "translator researcher" kind of research shows that the problems of non-equivalence are resulted from not only the author’s uses of local dialects and Arabic Islamic terms also the lexical and semantic field of the source words or expressions. More specifically the problems include cultural specific context, source text not lexicalized in target text, semantically complex source text, source text and target text making different distinction in meaning, differences in expressive meaning, differences in form, and loan words in source text. To make the translation of the text into English readable and relatable as possible, syntactic, semantic and pragmatic strategies are adopted.